(untitled) (Indonesian Journal of Cultural and Community Development, 2024)
Background: Effective communication is essential for nurturing children’s moral development, particularly in orphanages. Specific Background: This qualitative study investigates communication dynamics between four caregivers and 19 children at the Muhammadiyah Pagesangan Orphanage in Surabaya. Knowledge Gap: Limited research exists on communication methods used in orphanages, especially for children from diverse socioeconomic backgrounds. Aims: The study aims to analyze communication patterns in moral guidance within the orphanage. Results: Findings indicate that children employ both primary and secondary communication methods to connect with distant parents, facing challenges such as limited phone access and socio-economic barriers. Novelty: This research highlights unique communication challenges in orphanages and proposes that effective communication fosters a nurturing environment. Implications: By promoting a loving communication atmosphere, caregivers can enhance children’s emotional well-being and moral development, suggesting that communication is crucial for effective caregiving practices in orphanage settings. Highlights : • Communication Patterns: Emphasizes the need for understanding how caregivers interact with children. • Challenges: Identifies barriers faced by children in maintaining contact with parents. • Nurturing Environment: Highlights the role of effective communication in promoting emotional well-being. Keywords: communication, orphanage, moral development, caregivers, qualitative research